Counseling of COVID-19 Prevention in The New Normal Era for Santriwati in MTs Idzhaarul-Haq - Deden Winda S; Ai Fitri; Angrita Nursyahidah; Nurul Kamilatunnisa; Vidya Finanda (Indonesian Journal of Community Empowerment (IJCE), 2022)
Abstract : The widespread of coronavirus causes Indonesian and the world's society need to increase awareness about the importance of obeying the health protocol. Even though the new normal has been implemented in several areas, it does not mean the community is free from Covid-19. The purpose of this community service is to provide direction and counseling to prevent Covid-19 in the new normal era. The implementation of community service was carried out at MTs Idzhaatul-Haq in Ancol village by directly giving material containing information about covid-19 and new normal directives, distributing masks, and handsanitizers to the students. From the implementation of this community service, masks and handsanitizers have been given which are directly used by the students. Abstrak: Semakin meluasnya penyebaran virus corona menjadikan masyarakat Indonesia maupun dunia perlu untuk meningkatkan kesadaran tentang pentingnya menaati protokol kesehatan. Meskipun New Normal telah diberlakukan di beberapa daerah bukan berarti masyarakat telah terbebas dari Covid-19. Tujuan pengabdian masyarakat ini adalah untuk memberikan pengarahan dan penyuluhan pencegahan covid-19 di era normal baru. Pelaksanaan pengabdian masyarakat dilakukan di MTs Idzhaarul-haq kampung Ancol dengan cara memberikan materi berisi pemahaman dan informasi mengenai covid-19 dan arahan new normal secara langsung, pembagian masker, dan pemberian handsanitizer. Dari pelaksanaan pengabdian masyarakat ini telah diberikan secara nyata masker dan handsanitizer yang langsung digunakan oleh para santriwati.